2001
DOI: 10.1259/bjr.74.880.740331
|View full text |Cite
|
Sign up to set email alerts
|

Vesicoureteric reflux and renal scarring in Chinese children

Abstract: Vesicoureteric reflux (VUR) and renal scarring are commonly found in children with urinary tract infection (UTI). The prevalence of VUR and scarring may vary between racial groups. There are no published data on the prevalence of VUR and scarring in Chinese children with UTI. A retrospective, single-institution study was made of Hong Kong Chinese children aged less than 5 years with a documented UTI investigated by both micturating cystourethrography and dimercaptosuccinic acid scintigraphy. VUR was identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…In our study, boys with APN constituted a minority, a pattern similar to reports from Caucasian populations and contrary to the male predominance of UTI found in studies in Asian children [6,13,17]. The exact cause is not clear but early circumcision, commonly practiced in our male patients, may have a role in lowering the occurrence of UTI in boys.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In our study, boys with APN constituted a minority, a pattern similar to reports from Caucasian populations and contrary to the male predominance of UTI found in studies in Asian children [6,13,17]. The exact cause is not clear but early circumcision, commonly practiced in our male patients, may have a role in lowering the occurrence of UTI in boys.…”
Section: Discussionsupporting
confidence: 71%
“…Other ethnic groups reported different renal scarring prevalences, the highest being from Thailand and Ireland (59%), Taiwan (57%) and Brazil (55%) [11,12,13,14]. The lowest, yet still significant, were found in Australian 25%, Swedish (37%) and the Chinese children of Hong Kong (37%) [15,16,17]. Forty-four percent of a group of Indian children with APN developed renal scars on follow-up, a figure similar to ours [6].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Howard et al found 28% of boys with UTI had pyelonephritis. [7][8][9] In our study vesicoureteric reflux was noticed in 29.68% of children with first UTI who are younger than 5 years. In children above 5 years reflux was found in 7.14% of children.…”
Section: Discussionsupporting
confidence: 48%
“…In other countries with a predominately Caucasian population (Sweden and Australia), the prevalence is lower (24%-27%) [11,12]. Howard et al [13] reported the presence of VUR in 39% of symptomatic Chinese children with UTI. In our series of Arab children from Kuwait with first febrile UTI, VUR was present in 22% of patients.…”
Section: Discussionmentioning
confidence: 99%